Bridging global and microregional scales: ploidy distribution in Pilosella echioides (Asteraceae) in central Europe - Trávnícek, Pavel; Dockalová, Zuzana; Rosenbaumová, Radka; Kubátová, Barbora; Szelag, Zbigniew; Chrtek, Jindrich (Annals of botany, 2011)
BACKGROUND AND AIMS: A detailed knowledge of cytotype distribution can provide important insights into the evolutionary history of polyploid systems. This study aims to explore the spatial distribution of different cytotypes in Pilosella echioides at various spatial scales (from the whole distributional range to the population level) and to outline possible evolutionary scenarios for the observed geographic pattern. METHODS: DNA-ploidy levels were estimated using DAPI flow cytometry in 4410 individuals of P. echioides from 46 populations spread over the entire distribution range in central Europe. Special attention was paid to the cytotype structure in the most ploidy-diverse population in south-west Moravia. KEY RESULTS: Five different cytotypes (2x, 3x, 4x, 5x and 6x) were found, the last being recorded for the first time. Although ploidy-uniform (di- or tetraploid) sites clearly prevailed, nearly one-quarter of the populations investigated harboured more (up to all five) cytotypes. Whereas penta- and hexaploids constituted only a minority of the samples, a striking predominance of the triploid cytotype was observed in several populations. CONCLUSIONS: The representative sampling confirmed previous data on cytotype distribution, i.e. the spatial aggregation of mixed-ploidy populations in south-west Moravia and Lower Austria and the predominance of ploidy-uniform populations in other parts of the area investigated. Recurrent origin of polyploids from diploid progenitors via unreduced gametes and their successful establishment are considered the key factors promoting intrapopulational ploidy mixture ('primary hybrid zones'). As an alternative to the generally accepted theory of cytotype co-existence based on the development of different means of inter-ploidy reproductive isolation, it is suggested that a long-term ploidy mixture can also be maintained in free-mating populations provided that the polyploids originate with a sufficient frequency. In addition, the prevalence (or subdominance) of the triploid cytotype in several mixed-ploidy populations represents the first evidence of such a phenomenon in plant systems with exclusively sexual reproduction.
Keywords: průtoková cytometrie; DNA, Plant; Phylogeography; Evropa; Flow Cytometry; Asteraceae; Chromosomes, Plant; biologická evoluce; ploidie; genetická variace; fylogeografie; DNA rostlinná; Ploidies; Reproduction; Biological Evolution; Europe; rozmnožování; chromozomy rostlin; Genetic Variation